Application of low cost polyurethane (PU) foam for fabricating porous tri-calcium phosphate (TCP) - Abdul Rahman, Fariza; Ahmad, Zuraida; Iis, Sopyan (Trans Tech Publications, 2010)
Porous tri-calcium phosphate, well-known for its use as artificial bone, was prepared via sponge polymeric method by the application of low cost polyurethane (PU) foam as a structural guide. In this experiment, fractions of tri-calcium phosphate (TCP) are controlled at 12, 13, 14, 15 and 16 grams and mixed with distilled water (fixed at 25 grams) to produce slurries. Subsequently,rectangular shaped PU foam was immersed in the slurry and dried for three days. Samples were then sintered at 1100°C to obtain porous tri-calcium phosphate. This method produces porous tricalcium phosphate with porosity between 31-44% and the compressive strength in the range of 0.17-1.02 MPa. The macroporosity of the tri-calcium phosphate, observed through SEM, was in the range of 100 μm to 900 μm.